Al2O3/CrAlSiN multilayer coating deposited using hybrid magnetron sputtering and atomic layer deposition. Issue 9 (15th June 2019) - Dai, Wei; Wang, Qimin; Kim, Kwang-Ho; Kwon, Se-Hun
Abstract: In this study, Al2 O3 /CrAlSiN multilayer coatings with various periods were prepared using a hybrid process involving overlapping magnetron sputtering of CrAlSiN and atomic layer deposition (ALD) of Al2 O3 . The influence of the number of Al2 O3 layers on the mechanical properties, corrosion behavior and oxidation characteristics of the coatings was studied using nano/micro indentation, electrochemical corrosion, and high temperature static oxidation tests. The results show that the multilayer structure can effectively prevent crack propagation during the coating and subsequently increase the coating toughness. A substantial improvement in the resistance to electrochemical and oxidation corrosion was observed in the Al2 O3 /CrAlSiN multilayer coatings and increasing the number of Al2 O3 layers dramatically increases the corrosion durability. The Al2 O3 ALD layers are expected to inhibit the diffusion of corrosive substances such as ions and oxygen and the increase of the Al2 O3 layer number decreases the diffusion fluxes of the coating elements to the surface and limit the oxide growth, resulting in the evolution of the oxidation produces from irregular particles to nano-walls/fibers. It is supposed that the PVD/ALD hybrid process may open a new hard coating design concept by providing a superior toughness and corrosion/oxidation resistance.